The Effectiveness of Peer Educator Mentoring in Increasing Teenagers' Knowledge About The KRR Triad in The Tageh Youth Group in Bukittinggi City - Pramaswari, Amanda; Franzisca, Vani; Evareny, Lisma; Mesalina, Rosa (proceedinginternational, 2024)
In Indonesia, the incidence of teenagers experiencing TRIAD KRR cases is still high. 35.9% of teenagers have had free sex, 45.04% have used drugs, and 45.9% have been exposed to HIV/AIDS. One of the contributing factors is low knowledge and searching for wrong information regarding the KRR Triad. The aim of this research is to determine the effectiveness of peer educator mentoring in increasing teenagers' knowledge regarding the KRR triad. This type of research is analytical. The research design used was a quasi experimental one group Pre – Post Design. The research population was 534 teenagers aged 15-19 years, Birugo Village, Aur Birugo Tigo Baleh District, Bukittinggi City. The sample was 43, CI 95%, p value < 0.05. Data collection using questionnaire techniques uses questionnaire instruments that have been tested for validity. Respondents filled out questionnaires before and after mentoring by peer educators. Data were processed using univariate and bivariate analysis. The statistical test used was the Wilcoxon paired t test because the data distribution was not normal. Most respondents had low knowledge, namely 74.4% before mentoring. After mentoring, most respondents had high knowledge, around 53.5%. The statistical test results obtained a significant value of 0.019 (p ˂ 0.05), which means there is a significant difference in knowledge between before and after peer educator mentoring. Mentoring by peer educators can increase adolescent knowledge so that the implementation of programs to increase knowledge about the triad of adolescent reproductive health. Therefore, mentoring peer educators can be used as an effort to anticipate TRIAD for Adolescent Reproductive Health